Existential Approach towards Religion - Charles B. Berebon (INSIGHT: Indonesian Journal Social Studies and Humanities, 2022)
Abstract.It has been customary to see “existentialism” and “religion” as contradictory concepts, but I have shown in this work how, if we set aside extremism, we can see existential thought as a solution. Existentialism changes the focal point of thinking from “mass” to “man,” and that is the only definite thing about it. All else may vary from individual to individual; therefore, it provides a twofold solution. First, it presents a scope for man to indulge in, to quote Jacques Maritain (a theist existentialist), “transcendental subjectivity” without being bound to follow one or another kind of organized religion. The other is an existential approach towards others from the point of view of a second or third person; “I” understand that “Other” is not “I.” Thus, by mere acceptance of this fact, men can grow out of the obsession they have been indoctrinated with by their religions, i.e., “ours is the only way,” and may overcome the impact of “collective communal ego,” thus reaching a quick pragmatic way of peaceful co-existence. However, I have further discussed atheistic existentialists like Sartre, Camus, and Nietzsche himself, who give priority to living life as it is, with all its pleasures and suffering, without seeking finality or meaning. Finally, I have shown how Nietzsche, by means of his relentless attacks on superficial ideologies of “absolute certainty” and “beyond,” acts as a “gadfly,” who, although annoying, forces the coming generation of thinkers to think outside of the box.Keywords: Religion, existentialism, philosophy, Kierkegaard, Nietzsche